2005
DOI: 10.1007/s10886-005-5287-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sulfur Precursors and Volatiles Production by the Leek Allium porrum in Response to Specialist Insect Attack

Abstract: Abstract-To defend themselves against herbivory, plants use a variety of direct and indirect strategies involving induced increases in secondary substances. Species of the Allium genus (Alliaceae), such as the leek Allium porrum (L.), produce nonprotein sulfur amino acids derived from cysteine, i.e., alk(en)yl-cysteine sulfoxides that are precursors of volatile thiosulfinates and disulfides. These defend most species including the specialist leek moth, Acrolepiopsis assectella. We determined by measuring the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
(50 reference statements)
2
28
0
Order By: Relevance
“…In the current study, the quantity of alliin was increased in garlic seedlings pretreated with isolate 153 and challenged with Sc. A similar result was reported by Dugravot et al () in leek, where the quantity of nonprotein sulphur amino acids, the precursors of volatile thiosulphinates and disulphides, from leek was increased in association with leek moth induction of plant defence responses. Thus, endophytic bacteria 153 may potentiate garlic defence responses by enhancing the production of alliin.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the quantity of alliin was increased in garlic seedlings pretreated with isolate 153 and challenged with Sc. A similar result was reported by Dugravot et al () in leek, where the quantity of nonprotein sulphur amino acids, the precursors of volatile thiosulphinates and disulphides, from leek was increased in association with leek moth induction of plant defence responses. Thus, endophytic bacteria 153 may potentiate garlic defence responses by enhancing the production of alliin.…”
Section: Discussionsupporting
confidence: 89%
“…In the first study, Reddy et al (2002) found DMDS in the frass of P. xylostella that was attractive to C. plutellae and C. carnea in a Y-tube olfactometer setup. In the second, the parasitoid wasp D. pulchellus was attracted by a blend of odors coming from attacked leeks (that emit thiosulfinates) and odors of A. assectella larval frass (Dugravot et al 2005;Dugravot and Thibout 2006), the latter material being known to emit a high concentration of DMDS (Auger et al 1989a). Although DMDS appears to be present in interactions that involve sulfur-containing plants and their associate herbivorous species, little is known about its importance as a cue at the third trophic level (i.e., predators and parasitoids).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the artificial and natural damage to B. napus (L.) and B. juncea (L.) roots led to highest TMT activities in their leaves (van Dam et al, 2012). Existing data indicate that the physical conditions and herbivorous insects are extremely potent in the release of sulfur volatiles (Dugravot et al, 2005;Rouseff et al, 2008). In M. persicae-A.…”
Section: Discussionmentioning
confidence: 99%